PENINGKATAN MODEL PEMBELAJARAN INQUIRY LEARNING BERBANTUAN MEDIA PAPAN TAMBAH AJAIB TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS 2 SD. - Pertiwi, Tiara; Roestika Rini, Zulmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the differences and effects of implementing the Inquiry Learning model assisted by the "Papan Tambah Ajaib" media on the mathematical concept comprehension abilities of 2nd-grade elementary school students. The main problem underlying this study is the low conceptual understanding of students at SD Negeri Pagersari 02, which is still below the Learning Achievement Criteria (KKTP), as well as the learning process that tends to be teacher-centered without the use of concrete media. The research method used is a quantitative approach with an experimental method. Data collection instruments include tests (pretest and posttest), questionnaires, observations, and interviews. Data analysis techniques are carried out using the Independent Sample T-test to see differences between groups and the Simple Linear Regression test to determine the influence of variables. The research results indicate that there is a significant difference between the students' conceptual understanding abilities in the experimental class and the control class, proven by a calculated significance value of 0.001 < 0.05. Furthermore, the simple linear regression test produced a significance value of 0.027 < 0.05 and an F value of 5.778, which means that the Inquiry Learning model assisted by the Magic Addition Board media has a positive and significant effect on students' conceptual understanding abilities. Thus, the implementation of this model and media is very efficient and effective in improving the quality of mathematics learning in grade 2 elementary school.